FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TERJADINYA STROKE BERULANG PADA PENDERITA PASCA STROKE - Indah Permata Sari (Universitas Baiturrahim, 2016)
Background: Stroke is a condition that occurs when blood flow to a part of the brain which is suddenly distrupted. While recurrent stroke is a stroke that occurred after the first stroke occurs as a result of lack of self control from the patients and the low level of awareness of stroke risk factors. Stroke risk factors that cannot be modified: age, gender, family history of stroke, and the tribe. Stroke risk factors that can be modified: hypertension, heart disease, diabetes mellitus, hypercholesterol, obesity, smoking, alcohol consumption, unhealthy lifestyle, and stress. The risk factors of stroke that occurs in general: drugs, head and neck injury, and infection. Stroke risk factor for women: the use of oral contraceptives, pregnancy and childbirth, and menopause.Methods: This study was done by a Cross Sectional obsevation by using quantitative method, and data analysis done by using Chi Square test. The number of samples in this study is 50 people.The Result: Statistical test done by using Chi Square obtained ρ-value: 0.021 or p < 0.05 Ha accepted means there is a family history of stroke with recurrent strokes. Relationship between hypertension and recurrent stroke. The ρ-value: 0.048 or p < 0.05 Ha accepted which means that there is a relationship of smoking with recurrent strokes. The ρ-value: 0.039 or p < 0.05 Ha accepted which means that there is a relationship between stress and recurrent strokes. Based on the analysis of the data showed that factors associated with the occurrence of reccurrent stroke toward patients with post stroke is a family history of stroke, hypertension, smoking, and stress.